Augmented Reality Remedial Worksheet for Negative Numbers: Subtraction Operation - Periasamy, Elango; Badioze Zaman, Halimah (Visual Informatics: Sustaining Research and Innovations, 2011)
Augmented Reality Remedial Worksheet for Negative Numbers Subtraction Operation (AR2WN2) is a negative numbers subtraction operation worksheet involving two integers for students that need help in subject domain. AR2WN2 provides visualization of correct thinking process for remedial students of negative numbers subtraction operation with a useful meta-cognitive learning tool that helps them to follow, analyse and construct it as their own thinking via an algorithm. AR2WN2 include explanatory texts that support the algorithm which is animated step-by-step through the visualization of correct thinking process. Thus, this paper introduces a suite of visualizations spanning an algorithm for negative numbers subtraction operation, offering to stimulate discussion and debate on the pedagogical merits of this technique.